Long-Term Trends in PM10, PM2.5, and Trace Elements in Ambient Air: Environmental and Health Risks from 2020 to 2024 - Heba M. Adly; Saleh A. K. Saleh (Atmosphere)
This study aimed to assess the long-term trends in PM10, PM2.5, and hazardous trace elements in Makkah from 2020 to 2024, evaluating seasonal variations, health risks, and potential mitigation strategies. The results indicated that the PM10 concentrations ranged from a minimum of 127.7 ± 14.2 µg/m3 (2020) to a maximum of 138.3 ± 15.7 µg/m3 (2024), while PM2.5 levels varied between 100.7 ± 18.7 µg/m3 and 109.8 ± 21.3 µg/m3. A seasonal analysis showed the highest PM10 and PM2.5 levels during winter (147.8 ± 16.4 µg/m3 and 119.5 ± 21.7 µg/m3 in 2024, respectively), coinciding with lower wind speeds and reduced dispersion. Among the nine trace elements analyzed, Cr VI exhibited the highest increase from 0.008 ± 0.001 µg/m3 (2020) to 0.012 ± 0.001 µg/m3 (2024), while Cd and Ni also rose significantly. The excess cancer risk (ECR) associated with these pollutants exceeded the recommended threshold, with a strong correlation between PM10 and ECR (r = 0.85–0.93, p < 0.01). These findings highlight the need for enhanced air quality monitoring and sustainable urban planning. Future research should focus on identifying the dominant pollution sources and assessing the long-term health impacts to support evidence-based air quality management in Makkah.